Farmer business school with climate change and gender perspective: Learning and monitoring guide. - International Potato Center (International Potato Center, 2019)
The farmer business school (FBS) is a participatory action learning process that involves farmer groups participating in agricultural value chains. As part of capacity strengthening, FBS comprises a series of group‐based experiential learning activities over a production‐marketing cycle while interacting with other chain actors and stakeholders. As a tangible outcome of FBS, the farmer‐participants are expected to initiate or strengthen a business upon completing the FBS learning process. FBS aspires to more profitable pro‐poor farm business through market‐oriented innovations that enhance trust, coordination, and collaboration between farmers and other chain actors while empowering men and women farmers, thus ultimately contributing to sustainable livelihoods of targeted farming households.